Tecnologia de aplicação de agrotóxicos no controle de fitonematóides em soja - Corte, Gerson Dalla (2013)
The soybean crop (Glycine max) has great importance to the Brazilian economy. However, the production suffers various risks, especially to weed interference and deleterious effects of pests, diseases and recently nematodes. Among the main species found in soybean fields, the most important are Pratylenchus brachyurus, Heterodera glycines and Meloydogyne javanica. Due the lack of alternatives to nematodes control in soybean, more studies are required to evaluate technologies that enable to reduce yield loss from nematodes. Therefore, this study aimed to evaluate the effect of different application systems and chemical treatments for P. brachyurus and M. javanica control in soybean. For that, three experiments were carried out, one in field condition and two in controlled condition (greenhouses), during the growing season 2011/2012. The experimental design was a randomized block with split plot, where the main plots were allocated three application systems: 1 - seed treatment (ST), 2 in-furrow application + seed treatment (twice the rate) and 3 in-furrow application. The subplots were composed of different chemical treatments: 1 - Check, 2 Avicta Completo (abamectin + thiamethoxam + fludioxonil + metalaxyl-M + thiabendazole - 30 + 42 + 1.5 + 1.2 + 9 g a.i. ha-1); 3 - Cropstar + Derosal Plus (imidacloprido + carbendazim + thiram thiodicarb - 63 + 189 + 18 + 42 g a.i. ha-1); 4 - Top Standak (fipronil + thiophanate-methyl + pyraclostrobin - 30 + 27 + 3 g a.i. ha-1); 5 - Furadan 350 + FS Derosal Plus (carbofurano + carbendazim + thiram - 420 + 18 + 42 g a.i. ha-1). It was analyzed in the field experiment number of emerged plants, plant height and population of nematodes in the roots. In the experiments conducted inside the greenhouses were assessed plant height, leaf area, fresh and dry weight of shoot, fresh weight of roots, plant height, population of nematodes in the plants roots. The results showed that the combination ST + furrow application provided higher control of P. brachyurus and M. javanica. The association of ST + Furrow resulted in higher efficacy and residual period, especially to abamectin + thiamethoxam + fludioxonil + metalaxyl-M + thiabendazole and thiodicarb imidacloprid + carbendazim + thiram. The furrow application was more effective when compared to ST for abamectin + thiamethoxam + fludioxonil + metalaxyl-M + thiabendazole, considering the control of M. javanica. The treatment with abamectin + thiamethoxam + fludioxonil + metalaxyl-M + thiabendazole resulted in higher levels of control, with consistent benefits in plant development. The response of spray technology was dependent of the product characteristics and nematodes.